Why does the subject speak? Prejudgement in fieldwork with Naxalites and Hindu rioters - Chitralekha (The Journal of the Royal Anthropological Institute, 2017)
This article explores the shifting trajectory of dramaturgical encounters with 'subjects' in two disparate contexts of violence in contemporary India: Naxalites in jharkhand and Bihar; and participants in the 2002 riots in Gujarat. It argues that why (and thereby what) the subject speaks has to be located within the larger text of performances in the 'field', involving the prejudgement (in a Gadamerian sense) of both researcher and subject. Limits and possibilities to prior knowledges of both predetermine outcomes of interaction and inform the enterprise of doing theory in troubled contexts. Cet article explore la trajectoire sinueuse des rencontres dramaturgiques avec des « sujets » dans deux contextes de violence différents dans l'Inde contemporaine : des naxalites du Jharkhand et du Bihār et des participants aux émeutes de 2002 dans le Gujarat. Il explique que la raison pour laquelle le sujet parle (donc ce qu'il dit) doit être resituée dans le grand texte des performances sur le « terrain », impliquant le préjugé (au sens gadamérien) du chercheur aussi bien que du sujet. Les limites et possibilités des connaissances antérieures de l'un et de l'autre prédéterminent les résultats de l'interaction et informent le travail de théorisation dans les contextes troublés.